DESAIN PRIMER UNTUK AMPLIFIKASI GEN katG MULTIDRUG RESISTANCE TUBERCULOSIS (MDR-TB) DENGAN METODE POLYMERASE CHAIN REACTION (PCR) - Tedi Suryadi, Putu; Ratnayani, Ketut; Yowani, Sagung Chandra (Jurnal Kimia (Journal of Chemistry), 2014)
Tuberculosis, the world’s major diseases, is one of the emerging infectious disease. The tuberculosis problem has become complicated and burdensome due to the emergence of drug resistant such as isoniazid (INH) resistant strains of Mycobacterium tuberculosis . Mutation in katG gene is the main mechanism of INH-resistance in most strains. Amplification of M. tuberculosis katG gene was performance by using PCR for detect the mutation. A pair of specific PCR primers (forward and reverse) was the most important factor to limit the target region of amplification. Primer designing is preceedly carried out for producing the specific primer desired. The aim of this study was to design the specific primers for a fragment of katG gene. In silico primer design was carried out by using Clone Manager Suite 6. DNA sequence template used in this primer design was downloaded from www.ncbi.nml.nih.gov . M. tuberculosis H37Rv katG gene with genbank code X68081.1 was choosen. This study was successfully designed the forward primer (5' GAAGTACGGCAAGAAGCTCTC 3') and reverse one (5' CGTGATCCGCTCATAGATCG 3') which was length of 21 and 20 nucleotide, respectively. These pair of primers were meet the requirement of a good primer include primer length, Tm value, percentage of GC content, no hairpins, limited dimers and runs. In conclusion, the result of this research showed that the primer designed were acceptable to amplify the fragment of 724 bp of katG gene in silico.
Keywords: Primer Design, PCR, katG gene Mycobacterium tuberculosis, in silico, Clone Manager Suite 6